Securing softswitches from malicious attacks - Opie, Jake Weyman (Rhodes University, Faculty of Science, Department of Computer Science, 2007)
Traditionally, real-time communication, such as voice calls, has run on separate, closed networks. Of all the limitations that these networks had, the ability of malicious attacks to cripple communication was not a crucial one. This situation has changed radically now that real-time communication and data have merged to share the same network. The objective of this project is to investigate the securing of softswitches with functionality similar to Private Branch Exchanges (PBX) from malicious attacks. The focus of the project will be a practical investigation of how to secure ILANGA, an ASTERISK-based system under development at Rhodes University. The practical investigation that focuses on ILANGA is based on performing six varied experiments on the different components of ILANGA. Before the six experiments are performed, basic preliminary security measures and the restrictions placed on the access to the database are discussed. The outcomes of these experiments are discussed and the precise reasons why these attacks were either successful or unsuccessful are given. Suggestions of a theoretical nature on how to defend against the successful attacks are also presented.
Keywords: Internet telephony -- Security measures; Computer networks -- Security measures; Digital telephone systems; Communication -- Technological innovations; Computer network protocols; TCP/IP (Computer network protocol); Switching theory